An evaluation of the circulation of Palma Hall's entrances and lobby in relation to its accessibility for persons with disabilities - Pascua, Janella Marie; Florendo, Raquel B. adviser (Quezon City College of Home Economics, University of the Philippines Dilman, 2016)
This study evaluated the effectiveness of the circulation of Palma Hall, focusing on the entrances and lobbys accessibility for persons with disabilities (PWDs). It determined if the circulation of Palma Hall's entrances and lobby are generally accessible and if it complies with the building code standards. Along with the evaluation, this study determined the common problems faced by PWDs and provided recommendations on how to improve the design relative to the problems they experience. To acquire appropriate data, the researcher limited the sample to physically impaired persons which frequently used the aforementioned areas of Palma Hall. The sample chosen through purposive sampling included seven (7) UP Diliman students who attended classes in Palma Hall while having mobility deficiencies. Specifically, it encompassed one (1) wheelchair user and six (6) persons with limited walking abilities which made travelling more difficult for them. The researcher employed a descriptive research design. The respondents supplied relevant information during the survey and interview to provide a greater insight regarding their perceptions and preferences. The researcher also conducted site visits to observe the condition of the buildings accessibility routes. This study used the building's adherence to the Universal Design theory and compliance to the design policies provided by Batas Pambansa Bilang 344 - Accessibility Law as a basis for analyzing the consolidated data. Results showed that relative to the Accessibility Law, Palma Hall's entrances and lobby are not fully accessible for PWDs in terms of circulation. Answers given by the respondents generally suggest that the left entrance and lobby partially meets the needs of users with a wide variety of characteristics while the main and right entrances do not. The presence of numerous stairs and the lack of ramps turned out to be the users main concerns. This led to the recommendations of providing effective accessibility features like ramps, elevators, special walkways, and handrails.
Submitted June 2016.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Entrance halls -- Philippines -- Barrier-free design; Palma Hall (UP Diliman) -- Barrier-free design